Sulwe - Nyong'o, Lupita; Harrison, Vashti (New York : Simon & Schuster Books for Young Readers, 2018)
When five-year-old Sulwe's classmates make fun of her dark skin, she tries lightening herself to no avail, but her encounter with a shooting star helps her understand there is beauty in every shade.
Keywords: Self-acceptance -- Juvenile fiction; Blacks -- Juvenile fiction -- Kenya; Stars -- Juvenile fiction; Self-acceptance -- Fiction; Blacks -- Fiction -- Kenya; Stars -- Fiction; Kenya -- Juvenile fiction; Kenya -- Fiction